LUCY PEVENSIE’S CHARACTERIZATIONS IN C.S. LEWIS’ NARNIA: THE LION, THE WITCH, AND THE WARDROBE - Suwastini, Ni Komang Arie; Widasuari, Ni Wayan Dinda; Wahyuni, Luh Gede Eka; Visestayati, Ni Putu Andilia (Universitas Pendidikan Ganesha, 2020)
As literature reflects human life, the characterizations of a fictional character in a novel can be analyzed as the reflections of the subconscious of the character in Freud's psychoanalysis. The present study will describe the characterizations of Lucy Pevensie as the main character in C.S. Lewis’ Narnia: The Lion, The Witch, and The Wardrobe and elaborate on how the main character's subconscious as reflected through her characterizations affects the plot development of the novel. Through the application of close reading with the perspective of Freudian psychoanalysis, the present study reveals that Lucy Pevensie's curious, kind, curious, kind, truthful, caring, loyal, and brave characterizations are as reflections of her id, ego, and superego. They are affected by the behaviors and characters around her and set the plot in motion (starting from disjunction, trajectory, proleptic events, reversal, discovery, and ending). As the end of the plot was resolved with Lucy Pevensie's bravery that leads to the saving of Edmund Pevensie from his demise, Lucy Pevensie's characterizations and their effects on the plot development implies that the combination of instinct, observation of reality and a deep conscience can be beneficial for the greater good of the society.